Applied Linguistics. Reflections on an evolving discipline with a focus on publications in the journal TEANGA, The Journal of the Irish Association for Applied Linguistics, from 2001 to 2023 - Jennifer Bruen (Teanga: The Journal of the Irish Association for Applied Linguistics)
This study tracks the evolution of the content in a single applied linguistics journal, TEANGA, The Journal of the Irish Association for Applied Linguistics (TEANGA). The aim is to gain deeper insights into the nature of applied linguistics research. A second, related objective is to compare the research published in TEANGA with broader developments in the field of applied linguistics. Using elements of both quantitative and interpretative content analysis, the paper analyses the focal topics of the keynote and research papers published in the eight annual issues of TEANGA published between 2001 and 2023, together with those of the articles in the six single issue volumes which were also published during this time frame. The findings suggest that, in line with the discipline of applied linguistics more broadly, second and foreign language teaching and learning, including language teacher education, are a central focus of both the annual and special issues. A number of other sub-disciplines are also quantitatively significant. These include multilingualism and plurilingualism, discourse analysis, corpus linguistics, language policy and planning, and sociolinguistics. Reflecting the journal’s particular context, Irish-English bilingualism and Irish immersion education play an important role. No obvious trends were observed in terms of these particular broad areas either increasing or decreasing in importance. However, an evolution in terms of topic was observed within an individual area. The focus in this regard was placed on second and foreign language teaching and learning. The impact of technological advances and socio-political change resulting in increased linguistic diversity could be observed in developments in the use of Information and Communication Technology inside and outside of the classroom to support virtual exchange and informal language learning. A focus on a wider range of languages was also observed in the later papers. Limited evidence was found of some of the more niche and emerging areas in the broader field of applied linguistics such as social justice, raciolinguistics, artificial intelligence, ethics in linguistics research and multilingual sustainability. Implications of the findings are considered.